Temperature dependence of the flexibility of thermophilic and mesophilic flavoenzymes of the nitroreductase fold - Merkley, Eric D. (Oxford University Press, 2010)
A widely held hypothesis regarding the thermostability of thermophilic proteins states asserts that, at any given temperature, thermophilic proteins are more rigid than their mesophilic counterparts. Many experimental and computational studies have addressed this question with conflicting results. Here, we compare two homologous enzymes, one mesophilic (Escherichia coli FMN-dependent nitroreductase; NTR) and one thermophilic (Thermus thermophilus NADH oxidase; NOX), by multiple molecular dynamics simulations at temperatures from 5 to 100°C. We find that the global rigidity/flexibility of the two proteins, assessed by a variety of metrics, is similar on the time scale of our simulations. However, the thermophilic enzyme retains its native conformation to a much greater degree at high temperature than does the mesophilic enzyme, both globally and within the active site. The simulations identify the helix F–helix G ‘arm’ as the region with the greatest difference in loss of native contacts between the two proteins with increasing temperature. In particular, a network of electrostatic interactions holds helix F to the body of the protein in the thermophilic protein, and this network is absent in the mesophilic counterpart.